2020
DOI: 10.1088/1742-6596/1450/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changing superheat degrees on energy consumption in a split air conditioning

Abstract: Split air conditioning is the most widely used in the community for both commercial and domestic purpose. But it can cause inefficiency or waste of energy use by the system. For this reason, it is very important to keep the system working in optimum conditions to prevent wasteful use of energy by the air conditioning system. This research will re-investigate the effect of the superheat degree of refrigerant coming out of the evaporator on the system’s energy consumption. This research is conducted by analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The average superheat for conventional AC system was 5.7 K. The increase of superheat when water was used as the working fluid showed the highest power consumed by the AC. The findings of this study demonstrated the increase of the instantaneous power consumption recorded as the superheat increased which align with Ardita et al, [9] findings but different from findings by Qi [24].…”
Section: Superheat and Power Consumptionsupporting
confidence: 80%
See 2 more Smart Citations
“…The average superheat for conventional AC system was 5.7 K. The increase of superheat when water was used as the working fluid showed the highest power consumed by the AC. The findings of this study demonstrated the increase of the instantaneous power consumption recorded as the superheat increased which align with Ardita et al, [9] findings but different from findings by Qi [24].…”
Section: Superheat and Power Consumptionsupporting
confidence: 80%
“…Nevertheless, research conducted by Ardita et al, [9] has shown differences in their findings, indicating that an increase in superheat results in a corresponding rise in power consumption ranging from 0.03% to 0.1%.…”
Section: Renewable Energymentioning
confidence: 88%
See 1 more Smart Citation